2006
DOI: 10.1063/1.2213017
|View full text |Cite
|
Sign up to set email alerts
|

Efficient organic light-emitting devices using an iridium complex as a phosphorescent host and a platinum complex as a red phosphorescent guest

Abstract: We demonstrated efficient organic light-emitting devices (OLEDs) using a phosphorescent host/guest system consisting of bis(2-phenylpyridinato-N,C2′)iridium(acetylacetonate) [(ppy)2Ir(acac)] as a host and a platinum complex (Pt-SA-1) as a guest. The OLED using (ppy)2Ir(acac) film doped with Pt-SA-1 (1wt%) showed an ideal red emission via efficient energy transfer from the host to the guest. The external quantum efficiency of the device was as high as 8.3%. The driving voltage was significantly reduced compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…8-10 wt %) to ensure effective energy transfer. [20] Thus, in using the phosphorescent organometallic complexes as hosts, the emitting dopant concentration can be substantially reduced (e.g. 2 wt % in the present case).…”
Section: à2mentioning
confidence: 98%
“…8-10 wt %) to ensure effective energy transfer. [20] Thus, in using the phosphorescent organometallic complexes as hosts, the emitting dopant concentration can be substantially reduced (e.g. 2 wt % in the present case).…”
Section: à2mentioning
confidence: 98%
“…For example, Tsuzuki et al [13] reported an efficient red PHOLED, which could be driven at a low voltage of 4.4 V at 100 cd/m 2 ), with phosphorescent material bis(2-phenyl-pyridinato-N,C 2 ' ) iridium(acetylacetonate)[(ppy) 2 Ir(acac)] as the host and tris(1-phenylisoquinolinolato-C 2 ,N)iridium(III) as the guest. Meanwhile, they doped a platinum complex [2,2'-1,2-phenylenebis(nitrilomethylidyne) bis 4,6-di-tertbutylphenolate-N,N',O,O'] platinum(II) in the phosphorescent material (ppy) 2 Ir(acac) and obtained a maximum external quantum efficiency of 8.3% and a maximum current efficiency (η c,max ) of 4.9 cd/A at the same time [16] .…”
Section: Introductionmentioning
confidence: 98%
“…In order to solve the problems above, phosphorescent materials are expected to play the part of host, which is beneficial to the enhancement of carrier injection from the carrier transport layer to the host. There have been only a few reports on phosphorescent OLEDs based on phosphorescent host materials [5,[11][12][13][14][15][16] , and almost all of the reports have focused on monochromatic red OLEDs. For example, Tsuzuki et al [13] reported an efficient red PHOLED, which could be driven at a low voltage of 4.4 V at 100 cd/m 2 ), with phosphorescent material bis(2-phenyl-pyridinato-N,C 2 ' ) iridium(acetylacetonate)[(ppy) 2 Ir(acac)] as the host and tris(1-phenylisoquinolinolato-C 2 ,N)iridium(III) as the guest.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include a red-emitting device containing (Pt{2,2-[1,2-phenylenebis(nitrilomethylidyne)]bis(4,6-di-tert-butylphenolate)]}, which showed Commission Internationale de L'Eclairage (CIE) color coordinates of (0.68, 0.32) and λ max of 645 nm; [6] an orangeemitting device containing {Pt[(9,9-diethyl-7-pyridin-2-ylfluoren-2-yl)diphenylamine](acac)}, which has CIE coordinates (0.55, 0.45) and λ max 572 nm; [11] a white-emitting device containing {Pt[N, Nbis(salicylidene)-1,2-ethylenediamine]}, with CIE coordinates (0.33, 0.35) and λ max 448, 552 nm; [8] and a green-emitting device containing [Pt(pentafluorophenyl) 2 (4,7-diphenylphenanthroline)], with CIE coordinates (0.329, 0.551) and λ max 519 nm. [7] As 2a and 2b show luminescence at short wavelengths and strong luminescence intensity, they are suitable candidates for emitters in high-efficiency OLEDs.…”
Section: Electroluminescent Devicesmentioning
confidence: 99%